ANALISIS KENDALA PEMBELAJARAN KETERAMPILAN MEMBACA BAHASA INGGRIS DI SEKOLAH DASAR - Ramadhani, Alya Zulfa; Simajuntak, Eva Betty; Daulay, Pangadilan; Salwa, Nadhin; Tambunan, Gustyven; Hafidz, Rafiqi; Sinambela, Joya Salomita (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to analyze the challenges encountered in teaching English reading skills at the elementary school level. The research employed a qualitative descriptive approach and was conducted at a public elementary school in Binjai City. Data were collected through semi-structured interviews with an English teacher to obtain in-depth information regarding learning difficulties, instructional practices, and supporting factors in the classroom. The results indicate that students experience significant difficulties in English reading skills, particularly in phonological awareness, word pronunciation, contextual comprehension, and reading confidence. These challenges are influenced by several factors, including limited learning media and technological facilities, the dominance of teacher-centered instructional methods, low student motivation, and minimal parental support at home. The findings also reveal that inadequate exposure to English outside the classroom further hampers students’ reading development. This study highlights the importance of adopting a holistic approach that involves improving teacher competence, providing interactive and contextual learning media, and strengthening collaboration between schools and families. The results are expected to contribute to the improvement of English language instruction at the elementary school level and serve as a reference for developing more effective learning strategies.